1-Allyl-3-methyl-3 `,5 `-diphenylspiro[quinoxaline-2(1H),2 `(3 ` H)-[1,3,4]thiadiazole] - Anothane, C.A.; Bouhfid, R.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title spiro compound, C25H22N4S, the planar quinoxaline (r.m.s. deviation = 0.070 angstrom) and planar thiadiazole (r.m.s. deviation = 0.060 angstrom) ring systems share a common C atom; their mean planes are aligned at 89.7 (1)degrees. The thiazole ring possesses two aromatic ring substituents and is nearly coplanar with these rings [the dihedral angles between the thiadiazole and phenyl rings are 5.7 (1) and 10.7 (1)degrees]. The allyl unit is disordered over two positions in a 0.65 (1):0.35 (1) ratio.